Proceedings of the 2022 Conference on Empirical Methods in Natural Language Processing 2022
DOI: 10.18653/v1/2022.emnlp-main.481
|View full text |Cite
|
Sign up to set email alerts
|

FLUTE: Figurative Language Understanding through Textual Explanations

Abstract: Large Vision-Language models (VLMs) have demonstrated strong reasoning capabilities in tasks requiring a fine-grained understanding of literal images and text, such as visual question-answering or visual entailment. However, there has been little exploration of these models' capabilities when presented with images and captions containing figurative phenomena such as metaphors or humor, the meaning of which is often implicit. To close this gap, we propose a new task and a high-quality dataset: Visual Figurative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With the script representation, we describe how to embed a cultural norm into a sentence context to generate a premise and hypothesis pair. The structured representation of cultural norm allows us to leverage LLMs to generate premises and hypotheses, a promising approach to construct NLI datasets (Liu et al, 2022;Chakrabarty et al, 2022). Specifically, we first prompt ChatGPT/GPT-3.5turbo to generate premises and hypotheses from the script, followed by human editing on the generated content.…”
Section: Model-in-the-loop Generationmentioning
confidence: 99%
“…With the script representation, we describe how to embed a cultural norm into a sentence context to generate a premise and hypothesis pair. The structured representation of cultural norm allows us to leverage LLMs to generate premises and hypotheses, a promising approach to construct NLI datasets (Liu et al, 2022;Chakrabarty et al, 2022). Specifically, we first prompt ChatGPT/GPT-3.5turbo to generate premises and hypotheses from the script, followed by human editing on the generated content.…”
Section: Model-in-the-loop Generationmentioning
confidence: 99%
“…Here, we structure the identification of social norm differences across cultures as an explainable textual entailment task (a.k.a natural language inference (NLI)) similar to e-SNLI (Camburu et al, 2018); a difference in cultural norms equates to a contradiction between norms of different cultures for a given situation, and vice versa for entailment. Given the recent success of human-AI collaboration frameworks (Wiegreffe et al, 2022;Bartolo et al, 2022;Chakrabarty et al, 2022), the complex nature of Given an input Text, respond with Social Norms that are assumed by the speaker of the text, in English. Social Norms are rules and standards that are understood by members of a group, and that guide or constrain social behaviors without the force of law.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Prior work in interpretability (Wiegreffe et al, 2021) has shown that rationales from joint selfrationalizing models-predicting both the explanation alongside the relation label-are capable of producing faithful free-text rationales. Following prior work (Chakrabarty et al, 2022), we fine-tune a joint self-rationalizing T5 model in multiple settings, randomly splitting our data into 65% train, 10% validation, and 25% test set splits (Appendix Section C).…”
Section: Experiments and Evaluationmentioning
confidence: 99%
“…Numerous sources have been explored to capture figurative expressions (Chakrabarty et al, 2022;Liu et al, 2022b;Bizzoni and Lappin, 2018). Nonetheless, they often suffer from limitations in scale or cost.…”
Section: Data Collectionmentioning
confidence: 99%